Keamanan Cyber dan Peretasan Etis: Pentingnya Melindungi Data Pengguna - Fauzi, Achmad; Akbar, Rido; Rizkha, Adela; Tamiya Putri, Safira; Fadhilah, Intan; Putri Iskandar, Nadia; Ngurah Agung, I Gusti (Jurnal Ilmu Multidisiplin, 2023)
Cyber risk is a hazard or threat associated with the use of interconnected technology systems. This risk occurs when one or more of the three attributes of information namely confidentiality, integrity, and availability are affected. Basically, cyber risk is an operational risk that occurs in cyberspace. Somehow, cybersecurity mechanisms are expensive to implement. This study is to examine the importance of cybersecurity and the use of ethical hacking techniques for the protection of user data through globally defined characterizations. The method used is a literature review based on books, journals, and the internet.